2020
DOI: 10.1038/s41598-020-74478-y
|View full text |Cite
|
Sign up to set email alerts
|

Compostable, fully biobased foams using PLA and micro cellulose for zero energy buildings

Abstract: Ecological, health and environmental concerns are driving the need for bio-resourced foams for the building industry. In this paper, we examine foams made from polylactic acid (PLA) and micro cellulose fibrils (MCF). To ensure no volatile organic compounds in the foam, supercritical CO2 (sc-CO2) physical foaming of melt mixed systems was conducted. Mechanical and thermal conductivity properties were determined and applied to a net zero energy model house. The results showed that MCF had a concentration depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 136 publications
1
14
0
Order By: Relevance
“…Figure 12 , Figure 13 and Figure 14 , show the concept of foam injection molding, foam extrusion and bead foaming, respectively. Such foams exhibit thermal and mechanical properties comparable to those of the currently used petroleum-based foams [ 23 , 280 ]. An improvement of the morphology of the foam cell via modification of polymer melt viscosity is believed to be feasible through the addition of lignocellulosic fibers.…”
Section: Trends Of Pla and Phas Applicationsmentioning
confidence: 99%
“…Figure 12 , Figure 13 and Figure 14 , show the concept of foam injection molding, foam extrusion and bead foaming, respectively. Such foams exhibit thermal and mechanical properties comparable to those of the currently used petroleum-based foams [ 23 , 280 ]. An improvement of the morphology of the foam cell via modification of polymer melt viscosity is believed to be feasible through the addition of lignocellulosic fibers.…”
Section: Trends Of Pla and Phas Applicationsmentioning
confidence: 99%
“…The biodegradability of PLA [28][29][30][31][32] and its composites containing microsized cellulose [33][34][35][36][37] or nanocellulose [38][39][40][41][42] are well documented. These studies have shown that PLA is capable of biodegradation under both aerobic and anaerobic conditions and that it is more recalcitrant to biodegradation than polycaprolactone (PCL) and polyhydroxybutyrate (PHB).…”
Section: Introductionmentioning
confidence: 99%
“…61 Under controlled composting conditions at 58 °C (ISO 14855-2), PBS degrades slower with a longer incubation time compared to PεCL. 62 The intermediate 81 PLA + 3% microcellulose fibrils, 82 PLA + 5% clay, 83 PεCL at 25 °C, 84 PLA/PεCL/Thermoplastic starch (TPS) 60/10/30, 85 PεCL/HC 90/10, 86 PBAT/ PLA 60/40, 87 PBSA, 88 PBS, 89 PLA/TPS 50/50 and PBAT/TPS 43/57, 90 PBAT + 3% clay, 91 PHB/PεCL 75/25, 92 PHB, PHBV20, PHBV40, 93 PHB/cellulose 55/45, 94 cellulose, 82 PHBV + 3% clay, 91 PLA/TPS 60/40, 85 PBAT/TPS 60/40, 95 TPS, 96 rice starch, 97 PLA, and PLA/PHB 75/25 at 25 °C, 98 PεCL, 99 PεCL/cellulose acetate 80/20, 99 PεCL + 5% grape seed extract, 100 and PBS, PBS + 10% jute fibers. products in PBS degradation are 1,4-butanediol and succinic acid, which are readily metabolized by microorganisms through the citric acid cycle.…”
Section: ■ Compostability Of Polymersmentioning
confidence: 99%